Fine mapping and characterization of Fusarium wilt (Fusarium oxysporum f. sp. benincasae) resistance gene Fob1(t) in wax gourd (Benincasa hispida Cogn.) - Li, Fahuo; Qin, Jian; Li, Jingying; Cheng, Liang; He, Xuehan; Zhong, Xiaohui; Mo, Yangpeng; Liang, Han; Wang, Peng; Li, Yan; Wu, Yongguan (Frontiers in Plant Science, 2025)
Fusarium wilt (FW), caused by the plant fungus Fusarium oxysporum, causes severe economic losses in wax gourd (Benincasa hispida Cogn.). Developing disease-resistant varieties is an effective measure. Currently, no reports exist on gene localization or cloning of genes associated with FW resistance in wax gourd. However, our team has identified an FW resistance gene and plans to apply it in resistant varieties. In this study, we used bulked segregant analysis sequencing and quantitative trait locus detection on 1,304 inbred lines derived from resistant GD68 and susceptible HM25 parents to identify FW resistance genes. We successfully identified a resistance locus between the 3M13.385 and 3M16.869 markers on chromosome 3, named Fob1(t). Fine mapping between markers 3M15.904 and 3M16.373 (469 kb apart) identified 22 candidate genes. The transcriptome, sequencing comparison, and qRT-PCR analyses suggested that the endochitinase gene Bch03G006380 is the resistance gene, with significant expression differences between the parents and a one-base mutation in the first exon. The study also revealed the roles of Fob1(t) in plant hormones, transcription factors, phenylpropane metabolism, oxidation–reduction, disease progression, enzymes, and cell wall modification pathways, enhancing FW resistance in GD68. Finally, we identified two closely linked insertion–deletion markers that can assist in the transfer and utilization of the Fob1(t) gene, significantly improving the screening rate of positive individual plants and reducing breeding time.